DAMPAK PELAKSANAAN SEKOLAH LAPANG PENGELOLAAN TANAMAN TERPADU (SL-PTT) TERHADAP PENGETAHUAN, KETERAMPILAN, DAN SIKAP PETANI PADI SAWAH DI KECAMATAN KEPENUHAN - ranto, Muhammad (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2016)
Integrated Crop Management Field School (FFS-ICM) is a non-formal education opportunities for farmers to increase their knowledge and skills in recognizing the potential, farm plan, solve problems, make decisions and apply the appropriate technology. SL-PTT relationship with knowledge, skills, and attitudes can be seen after the implementation of SL-PTT. The purpose of this study was to determine the relationship SL-PTT with the knowledge, skills, and attitudes of rice farmers in the district Fullness Rokan Hulu. Analysis of the data used is the analysis of the average score. The results showed that the respondents knowledge before attending the SL-PTT 2.33 and after following the SL-PTT 4:35. Skills before joining SL-PTT 2.25 and after following the SL-PTT 4:33. Attitude before following SL-PTT 2:30 and after following the SL-PTT 4:29. Thus there is a change in knowledge, skills, and attitudes of farmers after training towards the better.